Are the Effects of Oral and Vaginal Contraceptives on Bone Formation in Young Women Mediated via the Growth Hormone-IGF-I Axis? - Allaway, Heather C. M.; Misra, Madhusmita; Southmayd, Emily A.; Stone, Michael S.; Weaver, Connie M.; Petkus, Dylan L.; De Souza, Mary Jane (Frontiers in Endocrinology, 2020)
Purpose: Combined hormonal contraceptive therapy has been associated with negative bone mineral density outcomes that may be route-dependent (i.e. combined oral contraception (COC) vs. contraceptive vaginal ring (CVR)) and involve the hepatic growth hormone (GH)/insulin-like growth factor-I (IGF-I) axis. The objective of the pilot study was to assess the impact of route of contraceptive administration on IGF-I and procollagen type I intact N-terminal propeptide (PINP) responses to an IGF-I Generation Test. We hypothesized that the peak rise in IGF-I and PINP concentration and area under the curve (AUC) would be attenuated following COC, but not CVR, use. Methods: Healthy, premenopausal women not taking hormonal contraception were recruited. Women were enrolled in the control group (n=8) or randomly assigned to COC (n=8) or CVR (n=8) for two contraceptive cycles. IGF-I Generation Tests were used as a probe to stimulate IGF-I release and were completed during the pre-intervention and intervention phases. Serum IGF-I and PINP were measured during both IGF-I Generation Tests. The study was registered at clinicaltrials.gov (NCT02367833). Results: Compared to the pre-intervention phase, peak IGF-I concentration in response to the IGF-I Generation Test in the intervention phase was suppressed in the COC group (p<0.001), but not the CVR or Control groups (p>0.090). Additionally, compared to the pre-intervention phase, PINP AUC during the intervention phase was suppressed in both COC and CVR groups (p<0.001), while no difference was observed in the control group (p=0.980). Conclusion: These data suggest that changes in recombinant human GH-stimulated hepatic IGF-I synthesis in response to combined hormonal contraception (CHC) use are dependent on route of CHC administration, while the influence on PINP is route-independent. Future research is needed to expand these results with larger randomized control trials in all age ranges of women who utilize hormonal contraception.